Peningkatan Kompetensi Pedagogik Guru Paud Menggunakan Tikar Monopoli Berbasis Lesson Study - Marwan Marwan; Misnar Misnar; Najmuddin Najmuddin; Intan Zuhra; Rahma Rahma (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2023)
Pedagogic competence must be mastered by Early Childhood Education teachers. The purpose of this study was to determine the pedagogical competence of PAUD teachers using lesson study-based Tikar Literasi and analyze using a mixed method. 50 early childhood teachers as the subject of this research. Nevertheless, Interviews and observation as the data collection. The results show that planning indicators are the preparation of curriculum tools, designing lesson study-based learning, and the use of Tikar Monopoli with a teacher confidence level of 85%. Learning achievement using Tikar Monopoli in the confident category is 92%, Lesson Study-based learning implementation indicators in the very confident category reach 90%, and learning achievement using Tikar Monopoli based on lesson study in the confident category is 87%. Thus the conclusion was the pedagogic competence of early childhood teachers is in category A (76-100), which means that the pedagogic competence of PAUD teachers using lesson study-based Tikar Monopoli is in the high category.